Cannabis-related Hospitalizations Among Youth in Canada Before and After Cannabis Legalization. Issue 3 (May 2021) - Auger, Nathalie; Luu, Thuy Mai; Ayoub, Aimina; Bilodeau-Bertrand, Marianne; Lo, Ernest; Low, Nancy
Abstract : Objectives: We investigated trends in cannabis-related hospitalizations among youth before and after legalization of recreational cannabis in Canada on October 17, 2018. Methods: We computed rates of cannabis-related hospitalizations and the proportion of substance-related hospitalizations involving cannabis by age and sex in the months before and after legalization in Quebec, Canada. Results: In boys aged 10 to 14 years, cannabis-related hospitalization rates increased from 5.2 per 100, 000 one year before legalization [95% confidence interval (CI) 2.9–9.3] to 9.5 per 100, 000 after legalization (95% CI 6.2–14.6), although the increase was not statistically significant. Cannabis was reported in 39.3% of substance-related hospitalizations in boys aged 10 to 14 years before legalization, compared with 70.0% after legalization, representing a difference of 30.7% (95% CI 2.8–58.6). There was no increase in cannabis-related hospitalizations among girls or boys aged 15 to 19 years. Conclusions: This study suggests that cannabis legalization in Canada did not increase the risk of short-term cannabis-related hospitalization among girls and older boys. However, legalization may have contributed to an increase in the risk in boys under 15 years. Further data are needed to clarify trends after legalization for younger adolescents. Abstract : Supplemental Digital Content is available in the text